Sistem Pendukung Keputusan Untuk Menentukan Kelayakan Penerima Bantuan Langsung Tunai Menggunakan Metode AHP-Topsis - Simatupang, Aidil Akbar; Hasugian, Abdul Halim (Universitas Budi Darma, 2025)
Social inequality and inaccuracy in aid distribution are still challenges in the Direct Cash Assistance (BLT) program, especially at the village level such as Bandar Selamat Village, North Labuhan Batu Regency. The process of determining BLT recipients which is still manual and subjective poses a risk of injustice and inefficiency. This study formulates the problem: how to develop an objective and targeted decision support system (DSS) for the selection of BLT recipients. The purpose of this study is to design and implement a DSS based on the Analytical Hierarchy Process (AHP) method and the Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) which can increase the accuracy and efficiency of aid recipient selection. The method used is Research and Development (R&D), with data collection techniques through interviews and observations, as well as comprehensive system testing. The results show that from 110 household head data, the system is able to identify 69 families eligible to receive assistance with a preference value ? 0.6. Employment and home conditions are the dominant criteria in determining eligibility. The system is proven to be consistent (CR = 0.0298 <0.1) and is able to simplify the decision-making process. This research provides real benefits in improving transparency, accountability, and effectiveness of social assistance distribution at the village level through a data and technology-based approach.